Job Interview Ethics - Naniek Risnawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Job interview is one of the processes in selecting prospective employees. This process is very important because the results of this interview determine the fate of job seekers. Preparing yourself before facing a job interview is very important in order to successfully win it. Job seekers need to have an understanding of how to win a job interview. It requires training on techniques for winning job interviews. When taking part in an interview session, applicants need to prepare themselves before the interview takes place, and how to answer questions, then continue with questions and answers and evaluation. Armed with knowledge about job interview ethics, applicants can prepare themselves and have the confidence to successfully win a job interview.